Selected Bioactive Compounds in Cereals and Cereal Products ̶ Their Role and Analysis by Chromatographic Techniques - Pihlava, Juha-Matti (fi=Turun yliopisto|en=University of Turku|, 2017)
Plants, including cereal plants, defend themselves against abiotic and biotic stress factors by various means. In addition to physical barriers there are a number of chemical defense systems in order to protect growing parts or seeds of plants against pathogens and herbivores. These protective chemicals are classified as secondary metabolites, and some of them, such as phenolic acids, lignans and flavonoids, are found in all major cereal crops. On the other hand, some of these defense chemicals are cereal-specific, such as hordatines in barley and avenanthramides in oats. Some, such as alkylresorcinols, are found in barley, wheat and rye, while benzoxazinoids are present only in wheat and rye. Interestingly, when the grains of cereals are used as food, these phytochemicals may act as health promoting, bioactive, compounds in humans. The main objective of this study was to gain new insight into certain less studied phytochemicals, e.g. flavonoids, benzoxazinoids and phenolamides such as hordatines, in cereals and cereal products. More basic research was carried out related to the content of avenanthramides, alkylresorcinols and lignans. In barley and beer, a number of phenolamides, namely hordatines, their agmatine precursors and their glycosides, were tentatively identified. The variation of these phenolamides and their sugar conjugates turned out to be surprisingly high. The content of hordatines in different beers was found to correlate positively with the alcohol content, although some non- or lowalcoholic beers could also contain relatively high concentrations of hordatines. Also, a new and interesting finding in beer was the spermidines conjugated with one or two hydroxycinnamoyl acids. A number of phenolamides, namely conjugates of spermidine, putrescine and agmatine, were also found in rye and rye products, and most of these were reported for the first time in this cereal. As a consecutive and supplementing work to our earlier study on rye milling fractions, a new study was conducted with a special focus on identification of flavonoids, lignans and benzoxazinoids, in addition to phenolamides. Based on the results of this work, the chemical diversity of the flavonoids in rye was found to be large, although the concentration of total flavonoids was relatively low. Flavonoids, phenolamides, lignans and benzoxazinoids were found also in rye products. Their presence in rye crisp breads, sourdough breads, malts and in a traditional Finnish food, mämmi, indicates that these compounds withstand relatively harsh conditions of various food processing operations. Probably the most intriguing finding was, however, that various benzoxazinoids can be found in wheat and rye beers and that even a non- or low-alcoholic wheat beer can be a relatively good source of dietary benzoxazinoids.

Kasvit, viljakasvit mukaan lukien, puolustautuvat abioottisia ja biottisia stressitekijöitä vastaan monin tavoin. Fysikaalisia suojamuureja vahvistavat lukuisat kemialliset puolustusjärjestelmät, jotka suojaavat kasvin kasvavia osia tai siemeniä kasvitauteja tai kasvinsyöjiä vastaan. Nämä suojaavat kemikaalit luokitellaan sekundaarimetaboliiteiksi, ja joitakin niitä, kuten fenolisia happoja, lignaaneja ja flavonoideja, löytyy kaikissa viljakasveista. Toisaalta jotkin näistä yhdisteistä ovat tyypillisiä vain tietyille viljoille, kuten hordatiinit ohralle ja avenantramidit kauralle. Joitakin yhdisteistä kuten alkyyliresorsinoleja esiintyy ohrassa, vehnässä ja rukiissa ja bentsoksatsinoideja vehnässä ja rukiissa. Käytettäessä viljaa ruokana näillä yhdisteillä voi olla terveyttä edistäviä vaikutuksia. Tutkimuksen tavoitteena oli lisätä tietoa viljojen ja viljatuotteiden vähemmän tutkituista pienkomponenteista, flavonoideista, bentsoksatsinoideista ja fenolamideista kuten hordatiineista. Lisäksi määritettiin myös avenantramidien, alkyyliresorsinolien ja lignaanien pitoisuuksia viljoissa ja viljatuotteissa. Ohrasta ja oluesta tunnistettiin alustavasti hordatiineja, niiden agmatiiniprekursoreita sekä glykosideja. Näiden yhdisteiden aglykoninen sekä niiden glykosidien lukumäärä osoittautui yllättävän korkeaksi. Hordatiinien kokonaispitoisuus oluissa oli verrannollinen alkoholipitoisuuteen, joskin suhteellisen suuria hordatiinipitoisuuksisa mitattiin myös alkoholittomista tai matala-alkoholisista oluista. Uutena mielenkiintoisena löydöksenä olivat oluessa olevat spermidiinit, joihin oli konjugoitunut yksi tai kaksi hydroksikanelihappoa. Fenolamideja, spermidiinin, putreskiinin ja agmatiinin fenolihappokonjugaatteja havaittiin myös rukiista ja ruistuotteista. Suurinta osaa näistä yhdisteistä ei ole aikaisemmin raportoitu löytyvän rukiista. Aikaisempaa rukiin myllyjakeita koskevaa työtämme täydennettiin uudella tutkimuksella, jossa keskityttiin erityisesti flavonoidien, lignaanien ja bentsoksatsinoidien tunnistamiseen edellä mainittujen fenolamidien lisäksi. Etenkin flavonoidien monimuotoisuus rukiissa oli suuri, vaikkakin niiden kokonaispitoisuus oli pieni. Koska näitä bioaktiivisia yhdisteitä havaittiin myös ruisnäkkileivistä, tuoreleivistä, maltaista sekä mämmistä, voidaan päätellä ko. yhdisteiden ainakin osin kestävän suhteellisen kovia ruuanvalmistusolosuhteita. Ehkä mielenkiintoisimpana löydöksenä oli kuitenkin vehnä- ja ruisoluiden bentsoksatsinoidit, joiden määrä alkoholittomissa tai matala-alkoholisissa vehnäoluissa voi olla merkittävä.